Fractional control of an industrial furnace - doi: 10.4025/actascitechnol.v32i3.6552 (Acta Scientiarum. Technology, 2010)
The requirements of high production allied with product quality, process safety and environmental regulation, lead control systems to play a key role in the operation of chemical and biochemical plants. In petrochemical plants, furnaces are essential equipments for process operation and due to energy costs, adequate operation and control are of extreme importance for process economics. The search for new and more efficient control laws led to the development of fractional PID control algorithm, which is based on the use of fractional differential equations. In this work, a previously identified mathematical model of an actual industrial furnace is used for fractional PID control studies. Feedback loop in servo control was analyzed, focusing on the study of the influence of the controller parameters over control loop performance. Particularly, P, fractional PI and fractional PD controller were considered in this study. Simulations were carried out showing that the fractional controllers were able to perform set-point transitions. The control loop performance was evaluated by ITAE and ISE criteria, showing that, in this study, fractional PI is the best algorithm.